1984
DOI: 10.1037/0735-7044.98.5.908
|View full text |Cite
|
Sign up to set email alerts
|

Chemosensory and hormonal mediation of social memory in male rats.

Abstract: The persistence with which adult male rats investigated a juvenile conspecific was significantly reduced following preexposure to either the juvenile or chemosensory stimuli (soiled bedding or urine) from that juvenile. The reduced persistence did not occur when the chemosensory stimulus came from a juvenile different from the one with which the subject was subsequently tested, which suggests the presence of a chemosensorily mediated social memory. It is suggested that any such memory may have adaptive value i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0
4

Year Published

1992
1992
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(59 citation statements)
references
References 10 publications
0
55
0
4
Order By: Relevance
“…Social discrimination in rats is regulated by the presence of olfactory cues (e.g. Sawyer et al, 1984), and investigation therefore takes the form of sniffing of the social stimulus, particularly focusing on the ano-genital region (Carr et al, 1976). The test is based upon a comparison of behaviour, particularly investigation, between two exposures of the same individual to a subject animal, separated by an inter-exposure interval (IEI).…”
Section: The Social Recognition Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Social discrimination in rats is regulated by the presence of olfactory cues (e.g. Sawyer et al, 1984), and investigation therefore takes the form of sniffing of the social stimulus, particularly focusing on the ano-genital region (Carr et al, 1976). The test is based upon a comparison of behaviour, particularly investigation, between two exposures of the same individual to a subject animal, separated by an inter-exposure interval (IEI).…”
Section: The Social Recognition Testmentioning
confidence: 99%
“…Studies have indicated that it is unlikely, however, that odour deposition, either by the adults on the juveniles, or by the juveniles in the home cages of the adults, influences the outcome of the social recognition test (e.g. Sawyer et al, 1984;Perio et al, 1989).…”
Section: The Social Recognition Testmentioning
confidence: 99%
“…70.5s: Burman & Mendl 2000). However, previous research has indicated that both urine and soiled bedding can be used successfully to replace live conspecifics as stimuli in social recognition tests (Sawyer et al, 1984). Post-hoc analysis, in which context data were pooled and data for experienced and inexperienced groups analysed separately, revealed that for those rats without …”
Section: Resultsmentioning
confidence: 97%
“…It therefore appears that olfactory cues are able to represent the identity of individual animals -as demonstrated by the substitutability of urine or soiled bedding as social stimuli for live animals in recognition tests (e.g. Sawyer et al, 1984).…”
Section: Odour Stimulimentioning
confidence: 99%
“…Kruczek 1998; an odour cue: e.g. Sawyer et al 1984) to a subject animal in order to encourage a habituation of stimulus investigation. The original 'habituation' stimulus and a 'novel' social stimulus are then introduced simultaneously, and stimulus investigation observed.…”
mentioning
confidence: 99%